Acellular dermal matrix contributes to epithelialization in patients with chronic sinusitis. (March 2019) - Bing, Zhong; Feng, Liu; Wu, Chun-Shu; Du, Jin-Tao; Liu, Ya-Feng; Liu, Shi-Xi
Background: Nasal endoscopic surgery is widely used for nasal diseases, including sinusitis and tumors. However, scar hyperplasia, nasal irritation, scab, and nasal obstruction delay nasal mucosal recovery, with prolonged cleaning exacerbating the patient's financial burden. Here, we presented a novel approach for the treatment of nasal mucosal defects, termed acellular dermal matrix. Methods: A total of 31 patients with bilateral chronic sinusitis (maxillary sinusitis and ethmoid sinusitis) underwent nasal surgery and nasal mucosal repair in September–October 2016. We divided the nasal cavities of each patient into control and acellular dermal matrix groups, randomly selected one side for nasal mucosal repair by surgery. A suitable acellular dermal matrix size was selected according to the defect in each patient. After pruning, the acellular dermal matrix was placed on the wound surface and filled with gelatin sponge. All patients were followed up for 14 weeks to compare nasal mucosal epithelialization between the control and acellular dermal matrix groups. Results： No obvious complications and adverse reactions were observed after nasal surgery. Lund-Kennedy scores in the acellular dermal matrix group were significantly decreased compared with the control group at 8 (0 (0, 1) vs. 2 (2, 4); P<0.05) weeks. Epithelialization time of eight weeks in the acellular dermal matrix groups was significantly decreased than the control group of 14 weeks. Conclusion: Acellular dermal matrix provides a growth framework for the healthy mucosa on the wounded surface and reduces postoperative epithelialization time.